Spinal dural and epidural arteriovenous fistula: Recurrence rate after surgical and endovascular treatment - Vercelli, Giovanni Giulio; Minardi, Massimiliano; Bergui, Mauro; Zenga, Francesco; Garbossa, Diego; Cofano, Fabio (Frontiers in Surgery, 2023)
Spinal dural arteriovenous fistula consist of an heterogenous group of vascular malformation often causing severe neurological deficit due to progressive myelopathy. This type of malformation could be associated with subarachnoid or subdural hemorrhage inside the spinal canal. In the English literature surgical treatment is regarded as the best option if compared to endovascular procedure, being the latter associated with an increased risk of relapse despite its less invasiveness. In this study a retrospective analysis of 30 patients with spinal dural and epidural fistula associated with perimedullary venous congestion was undertaken. The radiological and clinical presentation of each patient is analyzed, and the grade of myelopathy is classified through the mJOA score. A total number of 31 out of 41 collected procedures (22 surgery vs 19 endovascular) were dural fistulas while the remaining 10 were classified as epidural. A 46% recurrence rate for endovascular treatment against 0% for surgical (p-value 0,004) was described for dural fistule, while in the epidural fistula group the rate of recurrence was 80% and 20% respectively for endovascular and surgery treatment (p-value 0,6). According to the results, surgical treatment could be considered as first-line treatment for spinal dural arteriovenous fistulas. Endovascular embolization can be proposed in selected cases, as a less invasive technique, for elderly patients or with important comorbidities. In spinal epidural arteriovenous fistulas, in view of the greater invasiveness of the surgical treatment and the non-significant difference in terms of recurrence risk between the two techniques, endovascular treatment could be proposed as a first choice treatment; in the event of a recurrence, a surgical intervention will instead be proposed in a short time.